Identification of Transgender People With Cancer in Electronic Health Records: Recommendations Based on CancerLinQ Observations. Issue 3 (11th March 2021) - Alpert, Ash B.; Komatsoulis, George A.; Meersman, Stephen C.; Garrett-Mayer, Elizabeth; Bruinooge, Suanna S.; Miller, Robert S.; Potter, Danielle; Koronkowski, Becky; Stepanski, Edward; Dizon, Don S.
Abstract : PURPOSE: Cancer prevalence and outcomes data, necessary to understand disparities in transgender populations, are significantly hampered because gender identity data are not routinely collected. A database of clinical data on people with cancer, CancerLinQ, is operated by the ASCO and collected from practices across the United States and multiple electronic health records. METHODS: To attempt to identify transgender people with cancer within CancerLinQ, we used three criteria: (1) International Classification of Diseases 9/10 diagnosis (Dx) code suggestive of transgender identity; (2) male gender and Dx of cervical, endometrial, ovarian, fallopian tube, or other related cancer; and (3) female gender and Dx of prostate, testicular, penile, or other related cancer. Charts were abstracted to confirm transgender identity. RESULTS: Five hundred fifty-seven cases matched inclusion criteria and two hundred and forty-two were abstracted. Seventy-six percent of patients with Dx codes suggestive of transgender identity were transgender. Only 2% and 3% of the people identified by criteria 2 and 3 had evidence of transgender identity, respectively. Extrapolating to nonabstracted data, we would expect to identify an additional four individuals in category 2 and an additional three individuals in category 3, or a total of 44. The total population in CancerLinQ is approximately 1, 300, 000. Thus, our methods could identify 0.003% of the total population as transgender. CONCLUSION: Given the need for data regarding transgender people with cancer and the deficiencies of current data resources, a national concerted effort is needed to prospectively collect gender identity data. These efforts will require systemic efforts to create safe healthcare environments for transgender people.